Surabaya International Community Services: Climate Resilience through Community Empowerment in Surabaya - Fitriani, Nurina; Fatmawati, Fatmawati; Apsari, Retna; Megantoro, Prisma; Athari, Muhammad Hafizh (Universitas Diponegoro, 2024)
Universitas Airlangga is fully committed to participating in achieving the SDGs through carrying out community service-based research that includes multidisciplinary knowledge, both from the realms of science and technology and social humanities. This commitment is realized in the implementation of the Surabaya International Community Service program which aims to provide an understanding of global issues that affect society today regarding climate change and the current environment, introduce green energy technology to the international community and encourage the adoption of green energy as an alternative energy source, as well as building a network of cooperation and collaboration between participants from various countries and to overcome global environmental problems. Universitas Airlangga encourages full efforts in realizing the thirteenth point of the SDGs, namely Handling Climate Change through a series of community-based learning activities, mangrove rehabilitation, and dissemination of solar panels as green energy.